Identificação de áreas suscetíveis a inundações no perímetro urbano de Pato Branco - PR, por meio da integração SIG e AHP - Dalanhol, Isabel (2020)
Unplanned urbanization processes influence the occurrence of natural disasters. Among the phenomena that suffer interference are urban floods, which are the most common type of disaster and the one that hit the largest number of people around the world. These events have their recurrence increased due to the soil impermeabilization in urban areas. Thus, land use and land cover is an important factor for flood research in urban areas. Also, mapping urban flood-prone areas has been an alternative to disaster prevention and urban planning. However, the use of future land use and land cover scenarios for mapping urban floods is a factor that still requires investigation.Pato Branco city has been frequently affected by urban flooding. Thus, this research aimed to identify the areas susceptible to urban flooding in the southeastern region of the Ligeiro River Basin, located in the south of the urban perimeter of Pato Branco / PR city.For this purpose, the study used the integration of Geographic Information Systems (GIS) and the Analytic Hierarchy Process (AHP) when considering currentand future land use and land cover scenarios built by following the municipal legislation. The map of the current situation indicated the urban flood-prone areas and was consistent with the reality of the occurrences of this type of event in the city.The maps of future situations showed that the urban expansion of the city in the study area can contribute to the increase of flood-prone areas. The GIS software used proved to be a fast and efficient tool for mapping future land use and land cover scenarios. The AHP, on the other hand, was essential in ranking the important factors for urban flooding and in the construction of maps. The mapping carried out has been validated and can assist the municipality in urban planning and decision making regarding the choice of mitigation measures.